Effective Study of An Autonomous Hydroponic System Using Solar Energy and IoT Monitoring Technology - Siti Amely Jumaat; Ahmad Fateh Mohamad Nor; Ansar Jamil; Muhammad Nafis Ismail; Suriana Salimin; Muhammad Shafiq Bin Abdul Rahman (International Journal of Integrated Engineering, 2026)
This paper presents the development, and performance evaluation of a Solar Photovoltaic (PV)-powered Automatic Nutrient Mixing System integrated with IoT-based monitoring for sustainable agriculture. The system was tested under real environmental conditions to assess electrical performance, nutrient concentration control, and operational stability across multiple crop growth phases. The research site demonstrated suitable conditions for solar energy harvesting, with high annual Global Horizontal Irradiation with an average temperature of 27.2 °C, wind velocity of 1.7 m/s, and relative humidity of 83.8%. Electrical performance results indicated that PV voltage ranged from 26 V to 40 V, while battery voltage was consistently maintained between 25 V and 28 V. Output current varied proportionally with PV voltage, and the generated power reflected actual field conditions. The Automatic Mixing System successfully controlled Total Dissolved Solids (TDS) concentrations according to plant growth stages. Nutrient levels ranged from 500–800 ppm during vegetative stages and increased to 1000–1500 ppm during fruiting stages, meeting crop nutrient demands. Water level monitoring ensured accurate tracking of nutrient solution consumption, with timely manual replenishment preventing operational interruptions. Comparison with previous studies showed a small percentage error of 4–5%, validating the system’s accuracy and reliability. Overall, the integration of Solar PV energy with IoT-based nutrient management provides an energy-efficient, stable, and sustainable solution for precision agriculture, demonstrating strong potential for long-term smart farming applications.